Role of trained immunity in DCs and macrophages in the induction of Th2 responses and allergy treatment. What do we know? - Schiller, Hannah Ruth; Zeigermann, Carola; Schülke, Stefan (Frontiers in Immunology, 2026)
In a process termed trained immunity activated dendritic cells (DCs) and macrophages undergo distinct metabolic changes that contribute to their effector function: While certain activated DC subsets and M1 macrophages undergo a switch towards higher rates of glycolysis and a “disrupted Krebs cycle” to produce important immune effector molecules, alternatively activated (M2) macrophages, plasmacytoid DCs (pDCs), and conventional DCs type 1 (cDC1s) can rely on oxidative phosphorylation for their effector function. DCs and macrophages are also important cells in allergic reactions. While the induction of trained immune responses by microbial stimuli and vaccines is meanwhile well characterized, the contribution of trained immunity to either the establishment, elicitation, or treatment of allergic responses is largely unknown. In this context, recent results suggest distinct trained immunity responses to be established in allergic children. Here it seems that infections early in life predispose to the latter development of allergies, and trained immunity to also contribute to the immune modulation occurring in allergic patients during allergen-specific immunotherapy. Therefore, better understanding of trained immunity in these antigen-presenting cell (APC) subsets may allow to establish new biomarkers and enable a more targeted and efficient treatment of allergic diseases. This article summarizes the specific immune metabolic alterations observed in activated DCs and macrophages explaining their connection to DC and macrophage effector function. It then discusses our current knowledge on the contribution of trained immune responses in the establishment and treatment of allergic diseases.